2016
DOI: 10.1016/j.jdent.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Open access to journal articles in dentistry: Prevalence and citation impact

Abstract: Objectives: To investigate the current prevalence of open access (OA) in the field of dentistry, the means used to provide OA, as well as the association between OA and citation counts.Methods: PubMed was searched for dental articles published in 2013. The OA status of each article was determined by manually checking Google, Google Scholar, PubMed and ResearchGate. Citation data were extracted from Google Scholar, Scopus and Web of Science. Chi-square tests were used to compare the OA prevalence by different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 17 publications
2
32
0
5
Order By: Relevance
“…However, recent studies have shown that about 50% of biomedical research in general [5] and 60% of RCTs in dentistry [6] are behind the paywall. Healthcare professionals usually rely on abstracts to initially appraise a trial, decide whether or not to retrieve more information, or even directly inform their healthcare decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that about 50% of biomedical research in general [5] and 60% of RCTs in dentistry [6] are behind the paywall. Healthcare professionals usually rely on abstracts to initially appraise a trial, decide whether or not to retrieve more information, or even directly inform their healthcare decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…societies, universities, research institutions), (2) major commercial (Elsevier, Wiley-Blackwell, Springer Nature, Taylor & Francis, SAGE, Wolters Kluwer, Oxford University Press), and (3) other commercial publishers. Journals were categorized into two types: (1) open access journals (OAJs) which make all articles immediately OA, and (2) subscription journals that are only accessible to subscribers or readers who pay a pay-per-view fee, and usually available both in print and electronically [11,12]. Some subscription journals offer authors an option to pay and make individual articles OA ("hybrid OA" journals), or make selected or all articles freely available online after a set embargo period ("delayed OA" journals) [9,15].…”
Section: Data Extractionmentioning
confidence: 99%
“…The OA status of each included article was assessed in two rounds [11]. First, we searched the full title of each article (combined with the first author's surname when the title was too short or too broad) in four commonly used online search engines / databases: Google (only first 20 results examined);…”
Section: Assessment Of Oa Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Desde 2004, diversos estudios (de diferentes campos científicos) han informado que los artículos de OA se citan significativamente más que los artículos que no son de OA. Sin embargo, revisiones recientes señalan que estos estudios carecían de rigor metodológico (por ejemplo, falta de control de las variables) y que la "ventaja de la cita" que encontraron apareció como resultados de análisis inadecuados (Hua et al, 2016).…”
Section: Discusionunclassified